Comparison of Deep Breathing and Benson Relaxation on Decreasing Dismenore Pain in Adolescent Women at Bina Smp Indonesia Gemilang Boarding School - Noviasari, Rika; Yuliani, Indah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: determine the comparison of deep breathing relaxation and benson to decrease dismenore pain in young women. Methods: Quasi experimental with a two group pre test-post test design. The sample in this study were all young women who experienced pain during menstruation at SMP Bina Indonesia Gemilang Boarding School as many as 30 people. The sampling technique used purposive sampling. Results: The majority of menstrual pain before doing relaxation breathing in the majority was moderate pain (60.0%) and mild pain afterward (53.3%). The two treatments, namely deep breathing relaxation and benson, were both effective in reducing menstrual pain levels in young women (p. value 0.000). Conclusions: There is no difference between deep breathing relaxation and Benson relaxation in reducing the level of menstrual pain in young women. It is expected that young women who experience menstrual pain can do deep breathing relaxation or Benson relaxation to reduce the level of pain.